Racial/ethnic and educational differences in perceptions and use of a new urban trail. Issue 4 (19th May 2021) - Kraft, Amber N.; Nunez, Jessica; Tarlov, Elizabeth; Slater, Sandy; Zenk, Shannon N.
ABSTRACT : Objectives: Obesity and its associated health risks are on the rise throughout the US due, in part, to an overall decline in physical activity. Although public green spaces, and in particular trails, show promise as population-level interventions to promote physical activity among adults, these amenities may have disparate impacts across racial/ethnic and socioeconomic groups within a community. Design: This cross-sectional study employed an intercept survey of users of a newly opened 95 million rail-to-trail development in Chicago, IL, immediately after its opening and one year later to examine differences by race/ethnicity and educational attainment in trail use behaviors, motivations for trail use, safety concerns, and change in physical activity attributed to the trail. Results: Although the overall impact of the trail was positive, Latino users were more likely to report frequent use (4+ times/week), health motivations for using the trail, and increased physical activity attributed to the trail. However, Latino users were also more likely to indicate safety concerns and less likely to use areas of the trail in predominately white communities, even after controlling for community of residence. The least educated trail users frequented fewer trail areas and were less likely to indicate health motivations for trail use. Conclusions: Although urban trails represent an opportunity for cost-effective community-wide health promotion, they may not benefit all groups equally. Urban trails may have particularly promising benefits for Latino users, but safety concerns and the possibility of community racial segregation being replicated on trails should be addressed to maximize and sustain these benefits. Less educated residents in particular may not benefit from such projects as intended.